(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
This study examines the possibility of applying the turquoise management style at enterprises in modern Russia. What difficulties and positive aspects can both the employer and employees face. Can this management style exist in its pure form and does it have a future.